Pengaruh Massa Weight Roller terhadap Keausan Material dan Akselerasi Motor N-Max - Ghozali, Rahmatul; Putra, Randi Purnama; Abadi, Zainal; Arafat, Andril (Al-DYAS, 2024)
The Nmax motorbike roller basically consists of 6 units which function to maintain and regulate motor acceleration found in the Roller Housing in the Continuously Variable Transmission (CVT) section which allows friction and wear to occur on the roller material. Acceleration is the level of acceleration that occurs in an object at a certain time, while material wear is the mechanical property of an object to accept loads, power and energy without causing damage. This research was carried out using a Tribometer test tool and logger pro analysis software. The results obtained show that material wear increases with increasing RPM. At 500 rpm, standard roller wear ranges from 0.107% to 0.346%, while at 1400 rpm, wear increases to range from 0.323% to 0.938%. The acceleration test results show that the standard roller with a mass of 13 grams has the lowest acceleration performance, with the lowest value occurring in test II at 1.26 m/s². Meanwhile, the 9 gram roller has the highest average acceleration of 4.82 m/s².